Homo Economicus at School: Neoliberal Education and Teacher as Economic Being. Issue 1 (2nd January 2017) - Attick, Dennis
Abstract : This article extends the ongoing critique of neoliberalism's encroachment upon public education by highlighting how neoliberal ideas such individualism, accountability, governmentality, and the marketization of public life are recasting teachers today primarily as competitive economic beings. I contend that teachers are increasingly compelled to act as modern homo economici, working in an education system that conforms to the rules of the neoliberal market. As such, teachers are incentivized to act as self-entrepreneurs, rational individuals who are beholden to a governmentality that requires them to be accountable to the strictures of the neoliberal market. The neoliberal transformation of public schools has led to teaching becoming a strictly controlled and hyperindividualized entrepreneurial activity that compels teachers to focus on their own productivity, while rendering them eminently governable beings.